2013
DOI: 10.1088/1475-7516/2013/12/031
|View full text |Cite
|
Sign up to set email alerts
|

Interacting ghost dark energy models with variableGand Λ

Abstract: In this paper we consider several phenomenological models of variable Λ. Model of a flat Universe with variable Λ and G is accepted. It is well known, that varying G and Λ gives rise to modified field equations and modified conservation laws, which gives rise to many different manipulations and assumptions in literature. We will consider two component fluid, which parameters will enter to Λ. Interaction between fluids with energy densities ρ1 and ρ2 assumed as Q = 3Hb(ρ1 + ρ2). We have numerical analyze of imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 95 publications
0
38
0
Order By: Relevance
“…In order to obtain the coupling interaction equation we follow belove theoretical procedure. Based on the Friedman-Robertson-Walker metric, the interaction between dark matter and dark energy can be given as follows:where Q is arbitrary coupling function and subscript stands for a generic dark energy model to be specified 2341 . The conservation equations are subject to the Friedman constraint…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain the coupling interaction equation we follow belove theoretical procedure. Based on the Friedman-Robertson-Walker metric, the interaction between dark matter and dark energy can be given as follows:where Q is arbitrary coupling function and subscript stands for a generic dark energy model to be specified 2341 . The conservation equations are subject to the Friedman constraint…”
Section: Resultsmentioning
confidence: 99%
“…They fitted this model with observational data including SNeIa, BAO, BBN, the Hubble parameter data and found that the modified GDE model, without having the two fundamental cosmological puzzles, like the ΛCDM fit the astronomical data very well. Sadeghi et al (2013) discussed the flat universe model with varying G and Λ in the presence of modified GDE model (31). In (Karami et al 2013b), modified GDE scalar field models has been discussed in FRW universe with both interaction and viscosity.…”
Section: • Modified Gde Modelmentioning
confidence: 99%
“…In order to describe dark energy model, numerous studies have been performed in isotropic space-time such as scalar fields (quintessence, phantom, tachyon and etc.) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], modified gravity models [24][25][26][27][28][29][30][31], holographic models [32][33][34][35][36][37][38][39][40], interacting models [41][42][43][44][45][46][47][48][49][50][51][52], bouncing model [53][54][55...…”
Section: Introductionnmentioning
confidence: 99%